UPAYA MENINGKATKAN MINAT, MOTIVASI DAN HASIL BELAJAR LOMPAT JAUH GAYA HANG STYLE DENGAN MEDIA BOLA GANTUNG BAGI SISWA KELAS XI SMK: UPAYA MENINGKATKAN MINAT, MOTIVASI DAN HASIL BELAJAR LOMPAT JAUH GAYA HANG STYLE DENGAN MEDIA BOLA GANTUNG BAGI SISWA KELAS XI SMK - erwansyah erwansyah (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
The problem in this study is whether the use of hanging ball media in hang style long jump learning in physical education subjects can increase interest, motivation and learning outcomes of class XI students of SMK Negeri 1 Bungo. The purpose of this study was to increase interest, motivation and student learning outcomes in participating in the Hang Style long jump learning in class XI students of SMK Negeri 1 Bungo in the 2019/2020 academic year through hanging ball media. This research is a classroom action research. This study used 2 cycles, each of which consisted of: 1) planning; 2) implementation of the action; 3) observation; 4) reflection. The research carried out included 3 domains, namely the psychomotor domain, the affective domain, the cognitive domain. In addition, observations were made of the learning process during research activities and made a questionnaire in the form of a questionnaire on learning interest and motivation, to determine the extent of student satisfaction and interest in participating in learning using media. The results showed that the hang style long jump learning outcomes with hanging ball media in class XI SMK Negeri 1 Bungo had a positive impact, this was seen in the results of student learning completeness that exceeded the predetermined KKM, namely 75, experienced an increase, namely in cycle I learning completeness reached 73 , 53% while in cycle II learning completeness reached 91.18%. It can be concluded that learning the hang style long jump using hanging ball media can increase learning interest and motivation.